Microeconomic Theory - Wang, Susheng (Singapore : Springer Singapore : Imprint: Springer, 2018)
This book covers microeconomic theory at the Master's and Ph.D levels for students in business schools and economics departments. It concisely covers major mainstream microeconomic theories today, including neoclassical microeconomics, game theory, information economics, and contract theory.
Chapter 1. Producer Theory -- Chapter 2. Consumer Theory -- Chapter 3. Risk Theory -- Chapter 4. Equilibrium Theory -- Chapter 5. Micro-Foundation for Financial Markets -- Chapter 6. Micro-Foundation for Industrial Markets -- Chapter 7. Imperfect Information Games -- Chapter 8. Incomplete Information Games -- Chapter 9. Cooperative Games -- Chapter 10. Signalling -- Chapter 11. Mechanism Design -- Chapter 12. Incentive Contracts.
Description based on publisher-supplied MARC data.
Keywords: Education-Economic aspects; Game theory; Microeconomics; Microeconomics; Education Economics; Game Theory